Assessing the effects of trampling and bait-collecting on population, morphological and reproductive metrics of a key ecosystem engineer in Langebaan Lagoon - Madell, Kezia (Department of Biological Sciences, 2025)
Coastal sedimentary habitats, like Langebaan Lagoon, provide vital ecological and economic services that many human livelihoods rely upon. However, they are vulnerable to multiple human-related disturbances such as intense bait collection and trampling, that compromise ecosystem resilience and functionality. Research on how human disturbance impacts keystone species, such as the endobenthic sandprawn Kraussilichirus kraussi, an important ecosystem engineer, has proven to be valuable and effective in monitoring ecosystem health and improving ecosystem management. Knowledge of how human disturbance impacts these sandprawns is however, limited as it is primarily focused on population-level metrics such as abundance and morphology. Therefore, this study aimed to advance our understanding of how human disturbance impacts sandprawn populations, their reproduction, and the potential implications for the essential services they provide, across a spatial putative human disturbance gradient in Zone A, Langebaan Lagoon. Moreover, I aim to determine whether the reproductive responses of sandprawns can serve as novel, ecological indicators of benthic stress in intertidal sedimentary systems. The results demonstrate that sandprawn reproductive responses effectively indicate ecological stress. Increased human numbers correlate with increased sediment compaction and reduced dissolved oxygen concentrations. As an indirect result of these changes, there were significantly high percentages of sandprawn embryos which displayed abnormalities and arrested development in these sites with increased human numbers. However, at a sandprawn population-level, increased human numbers had no significant difference in sandprawn catch per unit effort and sandprawns had better body conditions at these sites. These findings suggest resource trade-offs as a response to low sediment oxygen, in which sandprawns in highly disturbed sites shift resources from reproduction to prioritise self-maintenance and survival. Recent literature has shown a growing interest in using keystone sandprawns as ecological stress indicators and this study further expands on this idea by linking human recreational disturbance to their reproductive biology of sandprawns. Adverse effects on sandprawn reproductive outputs are a cause of great concern, as chronic legacy effects of recreational disturbance may lead to population-level consequences, and thus compromise the vital ecological functions that these crustaceans provide. These effects are likely further exacerbated in intertidal systems with high frequencies of human disturbance and lack of management/regulation of human numbers. Overall, further research which links human disturbance to sandprawn reproduction in other coastal ecosystems is crucial to improving our understanding of this phenomenon and our future management of these systems.